2004
DOI: 10.1074/jbc.m310097200
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Topors Is a RING Finger-containing Protein That Functions as a Ubiquitin-protein Isopeptide Ligase for the Hairy Basic Helix-Loop-Helix Repressor Protein

Abstract: Transcriptional repression plays an essential role in many aspects of metazoan development. Drosophila hairy is a primary pair-rule gene encoding a basic helixloop-helix class transcriptional repressor that is required for proper segmentation. Previous characterization of Hairy-binding proteins has implicated two different classes of histone deacetylase as mediators of Hairy repression. Here, we present the characterization of a novel Hairy-interacting protein (dTopors) that binds specifically to the basic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Precedent for such a dual-activity protein is provided by the conserved RING-finger protein, Topors. Topors binds DNA topoisomerase I [50] and p53 [51,52] and it displays both Ub E3 ligase [53,54] and SUMO ligase activity [55]. Topors Ub ligase activity is dependent on its RING-finger domain, while its SUMO ligase activity is not [55].…”
Section: Discussionmentioning
confidence: 99%
“…Precedent for such a dual-activity protein is provided by the conserved RING-finger protein, Topors. Topors binds DNA topoisomerase I [50] and p53 [51,52] and it displays both Ub E3 ligase [53,54] and SUMO ligase activity [55]. Topors Ub ligase activity is dependent on its RING-finger domain, while its SUMO ligase activity is not [55].…”
Section: Discussionmentioning
confidence: 99%
“…This localization was consistent with recombination mapping of nbl to the region between pr and px. Additional complementation tests revealed that Df(dtopors AA ), a small deletion that removes dtopors and the adjacent gene prod (Secombe and Parkhurst 2004), failed to complement the nuclear and chromosome segregation defects of nbl. Furthermore, an insertional mutation in dtopors, P(Bac{WH}Topors f05115 , failed to complement nbl, whereas an insertional mutation in prod, P{lacW}prod k08810 , fully complemented.…”
Section: Mapping Nbl Mutationsmentioning
confidence: 99%
“…In addition to the EMS-induced alleles, we made use of an existing deletion, Df(dtopors AA ) (Secombe and Parkhurst 2004), and a piggyBac insertion allele, dtopors f05115 . Conceptual translation of the piggyBac insertion allele sequence predicts that it encode a protein truncated after amino acid 47 and therefore is likely a null allele.…”
Section: Mutations In Dtopors Disrupt Segregation Of All Chromosomes mentioning
confidence: 99%
See 1 more Smart Citation
“…Because TOPORS is a known E3 ubiquitin ligase for the transcription factors p53 (23) and Hairy (29), we sought to determine whether TOPORS can also ubiquitinate NKX3.1. In the presence of ubiquitin, E1, and E2 (UbcH5a) enzymes, TOPORS induced the appearance of higher molecular weight species of NKX3.1 (Fig.…”
Section: Topors Interacts With and Ubiquitinates Nkx31-tomentioning
confidence: 99%